Do IMF Programs Improve Economic Governance? - Honda, Jiro (IMF Working Papers; Working Paper ;, 2008)
This paper examines the effects of IMF financial assistance on economic governance in developing countries, based on panel data analyses of perceived governance indicators. It uses a two-stage approach to address possible endogeneity issues. The results show that successful implementation of IMF programs is associated with improvements in the quality of economic governance. Specifically, the paper finds statistically robust results that IMF concessional programs through the Poverty Reduction and Growth Facility tend to enhance the rule of law and strengthen control of corruption. Through this exercise, however, no statistically significant effect is observed for assistances under the General Resource Account.